Et si nous pouvions interviewer le boson de Higgs ? - Giulia Gaddi (Ateliers d'Anthropologie)
This contribution takes up the plastic anthropology exercise by offering a science fiction (or linguistics fiction) short story, “Un dialogue particulier”, in which the author imagines an ethnography of the Higgs boson: an elementary particle whose existence was confirmed by the European Organisation for Nuclear Research (CERN) in 2012 with the world’s largest particle accelerator, the Large Hadron Collider (LHC). This short story is followed by commentary entitled “Author’s note: How does one converse with a particle?”, in order to reveal the anthropological themes underlying its writing artifice.